To Clot or Not: HELLP Syndrome and Disseminated Intravascular Coagulation in an Eclamptic Patient with Intrauterine Fetal Demise - Justin Walker; Anthony Bonavia (Case Reports in Anesthesiology)
A 39-year-old G2P1001 female presented from an outside hospital following an eclamptic seizure in the setting of HELLP syndrome. This condition was complicated by intrauterine fetal demise and disseminated intravascular coagulation, which required an emergent cesarean section. We report the work-up and intraoperative and postoperative management of this complex patient with multiple medical needs. We focus on the hemostatic abnormalities in this patient and describe how our management would differ from that of a similar, nonpregnant patient.